21th Century Skills Based on Anticorupsy Education in Vocational School Prevention Strategy - Martini, Eneng; Komalasari, Kokom; Saripudin, Udin; Budimansyah, Dasim (International Journal of Psychosocial Rehabilitation, 2020)
Vocational education is directed so that the graduate becomes a skilled person in an area of expertise, and is ready to pursue a career in the world of work. While the purpose of this paper is to explore the anti-corruption education in vocational schools associated with PPKn subjects in the 21st century. The methods used in writing This is a literature study on several sources of books, journals and other references that support, from the results of theoretical studies it can be concluded that anti-corruption education in vocational schools through PPKn subjects in the 21st century must improve citizenship competencies in which there are three dimensions namely citizenship knowledge, citizenship skills and the disposition of citizenship that must be balanced with the needs of 21st century skill-based education, in order to face the global world with a full sense of responsibility and based on Pancasila values.